(untitled) (Fiep Bulletin - online, 2011)
Introduction: traffic accidents were responsible for over 50,000 deaths in 2007. In the context of TAs, vehicle-pedestrian collision incidents constitute one of the most frequent accident types, generating expenses of approximately 11 million reais with victim hospitalization in 2005 in São Paulo (RAMOS, 2008). Objectives: to identify vehicle-pedestrian collision victims attended to in the urgency service in Natal/RN; to identify body regions most often affected by the events. Methodology: it’s an exploratory descriptive study, with a quantitative approach and prospective data, performed in the urgency units in Pronto Socorro Clóvis Sarinho (PSCS), with protocol #016/07. The used inclusion criteria were: victims of vehicle-pedestrian collision of both genders, aged over 18 who accepted to take part in the research. The population consisted of 30 victims of running over, 19 (63.3%) were male; 13 (43.3%) were single. Regarding injuries by body region, 59.0% of the victims had injuries in the limbs/pelvic waist, followed by the face with 15.0%; head/neck with 06.0%. Conclusion: it’s crucial to know who the victims are and which body regions are most often hit by the event, so health education programs can be created which can transform behavior in traffic.